Pengaruh Citra Perusahaan PT. Garuda Indonesia Terhadap Loyalitas Pelanggan - farhan ghulaman; kresno yulianto (Inter Script : Journal of Creative Communication, 2021)
Getting customer loyalty is not easy, there are various ways that companies use to gain loyalty by distributing the right price to customers for the development of the company's image. PT. Garuda Indonesia is one of the companies affected by the company's image due to smuggling cases that affect customer loyalty on December 17, 2019. The purpose of this study was to determine the effect of corporate image on customer loyalty. This study uses a positivistic paradigm with a quantitative approach which is distributed through a questionnaire. The results of this study explain that Ha, which states that there is an influence between the variables of the corporate image of PT. Garuda Indonesia towards customer loyalty is accepted. So, Ho states that there is no influence between the variables of the image of the company PT. Garuda Indonesia against customer loyalty was rejected. So it can be concluded that there is a positive and significant influence between the variables of the corporate image of PT. Garuda Indonesia towards customer loyalty.